Common vampire bat attacks on humans in a village of the Amazon region of Brazil - Schneider Maria Cristina; Aron Joan; Santos-Burgoa Carlos; Uieda Wilson; Ruiz-Velazco Sílvia (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2001)
Many people in Amazonian communities have reported bat bites in the last decade. Bites by vampire bats can potentially transmit rabies to humans. The objective of this study was to analyze factors associated with bat biting in one of these communities. A cross-sectional survey was conducted in a village of gold miners in the Amazonian region of Brazil (160 inhabitants). Bats were captured near people's houses and sent to a lab. Of 129 people interviewed, 41% had been attacked by a bat at least once, with 92% of the bites located on the lower limbs. A logistic regression found that adults were bitten around four times more often than children (OR = 3.75, CI 95%: 1.46-9.62, p = 0.036). Males were bitten more frequently than females (OR = 2.08, CI 95%: 0.90-4.76, p = 0.067). Nine Desmodus rotundus and three frugivorous bats were captured and tested negative for rabies. The study suggests that, in an area of gold miners, common vampire bats are more likely to attack adults and males. The control strategy for human rabies developed in this region should therefore place special emphasis on adult males. There should also be more research on how the search for gold in the Amazonian region places people and the environment at risk.